Sensibility: a New Focus in Sámi Health Care Education - Nymo, Randi (The Australian Journal of Indigenous Education, 2007)
Abstract Colonialism has had significant bodily impacts on Indigenous peoples through medicine. Excluded from the German race, Sámi have been burdened by mainstream prejudices which perpetuate myths about Sámi having poor genetic material and, as a consequence, having an inferior culture and language. This offensive burden and subsequent humiliation has particular implications for the Sámi who come into contact with the health system as patients. Ethnic identity is connected with taboos, not only for patients, but also for Sámi and non-Sámi treaters. According to common knowledge Sáminess should not be a theme. In spite of intense assimilation, many Sámi understand illness as something caused of powers in nature or influenced by other people. The result can be a feeling of bodily chaos. Not understanding the meanings of the signs shown by the patients may bring health workers to interpret expressions of culture as signs of disease. Sámi patients can be diagnosed as suffering from delusions. Sometimes they are visited by traditional healers in faith to restore bodily cosmos. What’s more, the patient trying to hide her Sámi origin can be considered as dishonest. Sensing this staff may discharge her from hospital earlier and spoil her chances to get proper treatment. Health educators have specific responsibilities to make students aware of the diversity of patient’s culture and view of life. Within thought of body phenomenology the experiencing body is both subject and object. Messages are filtered by a cultural framework and the persons in interaction impact on each other. Face-to-face with the patients you can sense their vulnerability and decide to meet them as objects for your therapy activities or as individuals.